IN SEARCH OF EXISTENCE: CHINGIZ AITMATOV’S PHILOSOPHY OF MAN - Makhamatov, Makhamatovich; Polyakova, Rauza; Balandina, Lolita; Malyugina, Nadezhda; Ganina, Elena (Revista Inclusiones, 2020)
In this article, the authors have carried out the first study of the existential and philosophical ideas in Chingiz Aitmatov’s work and revealed previously obscure forms in which existence manifests. The authors substantiate the idea that the great Kyrgyz-Russian author expanded and developed F. Dostoevsky’s, A. Camus’, K. Hamsun’s and G. Marquez’s traditions of the literary existential philosophy in his work. The success of the study is due to the application of methods of hermeneutics, systematic-comparative analysis and philosophic generalization. Based on the analysis of episodes from Aitmatov’ various works and the comparison of the episodes with philosophical principles of existentialism, the authors conclude that the manifestations of the existential principle have been revealed in completely different phenomena of the human world and nature, spiritual and physiological being, be it children, animals, death, moral choice, etc. The forms of existences discovered during the study do not occur in works by prominent existentialists. The discovery of existential philosophy in Aitmatov’s works justifies the conclusion that he was not only one of the great humanist writers but also a philosopher-writer who contributed substantially to the philosophy of existentialism.